234k views
4 votes
18 (8 + 9t) - (t2 + 4) (2 – 3t)

The simplified expression is a polynomial.
The simplified expression has a constant term.
The simplified expression is cubic.
The simplified expression has four terms.
The simplified expression is a trinomial.

2 Answers

2 votes

Answer:

=3t3−2t2+174t+136

Explanation:

Let's simplify step-by-step.

18(8+9t)−(t2+4)(2−3t)

Distribute:

=(18)(8)+(18)(9t)+3t3+−2t2+12t+−8

=144+162t+3t3+−2t2+12t+−8

Combine Like Terms:

=144+162t+3t3+−2t2+12t+−8

=(3t3)+(−2t2)+(162t+12t)+(144+−8)

=3t3+−2t2+174t+136

User Chau Tran
by
4.6k points
3 votes

Answer: a, b, c, & d

Explanation:

18(8 + 9t) - (t² + 4)(2 - 3t)

= 144 + 162t - (2t² - 3t³ + 8 - 12t)

= 144 + 162t - 2t² + 3t³ - 8 + 12t

= 3t³ - 2t² + 174t + 136

a) The simplified expression is a polynomial. TRUE (there are many terms)

b) The simplified expression has a constant term. TRUE (136 is the constant)

c) The simplified expression is cubic. TRUE (the degree is 3)

d) The simplified expression has four terms. TRUE

e) The simplified expression is a trinomial. FALSE (there are 4 terms, not 3)

User Akash Rajbanshi
by
5.1k points